(3GdGSJHUGQ ajeG GNJda ef GdCNHGQs - (3GdWhSj, CHh LYaQ, eMeO Hf GdMSf Hf Ydj, J (B460(3g`s
(3ChdgG (B:s
(3eHJhQI GdChd, hChd GdehLhO efgG(B: ...(3Yf CHj HUjQ bGd (B...(3Ef GdehJhQ Cgdg heGdg ef VjY UdGI GdYUQ(B...s
(3BNQgG (B:s
(3eHJhQI GdBNQ, hBNQ GdehLhO efgG(B: (3HGH MO GdfHGT (B...(3bGd SeYJ CHG YHO Gddg Ydjg GdSdGe jbhd MO GdfHGT MO GdSGQb(B...s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B:(3L(B6(3,U(B85s
(3GdPQjYI(B:(3L(B2(3,U(B43s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdMOjK hGdeUWdMs